Botryoidal platinum, palladium and potarite from the Bom Sucesso stream, Minas Gerais, Brazil: Compositional zoning and origin - Fleet, M. E.; De Almeida, C. M.; Angeli, N. (Mineralogical Associação Canada, 2002)
Platinum-Pd nuggets from the Born Sucesso stream alluvium Minas Gerais, Brazil. have been investigated by electron-probe microanalysis. The nuggets attain 1 mm in maximum dimension and have a botryoidal habit, with pronounced compositional core-to-margin zoning of internal structures, Although there is a wide variation in internal morphology and individual zones vary markedly in thickness (<1-100 mum), a typical composite arborescent nugget comprises a broad irregular core region of massive auriferous Pd-Hg alloy (potarite delta-PdHg) or cavity space + relict potarite enclosed by a narrow zone of platiniferous, palladium or alloy of near Pt50Pd50 composition, and is progressively oscillatory zoned by palladian platinum, with growth eventually enveloping the whole botryoidal colony, to a narrow rim of palladian platinum or pure platinum. Other nuggets comprise an arborescent to dendritic core of auriferous potarite, a broad internal zone of either pure platinum or palladian platinum, and a narrow rim of platinum, the mineral palladium contains up to about 65 at.% Pd; this is the first detailed modern confirmation of palladium in its type locality. Auriferous potarite ranges in composition from similar toPd(3)Hg(2) to near Pd(Hg,Au). The origin of these nuggets remains unclear, but their mineralogy is broadly equivalent to that of palladian gold. potarite and platinum in alluvial sediments and overburden from Devon, England, which are considered to be detrital, and their platinum-group-clement geochemistry is consistent with precipitation from hydrothermal fluids. We suggest that the Bom Sucesso nuggets resulted from high-level episodic hydrothermal alteration of mafic and ultramafic rocks within the drainage basin, with the remobilized Pt and Pd precipitated in open spaces in the enclosing metaquartzites.
Keywords: platinum; palladium; potarite; botryoidal nuggets; alluvium; Bom Sucesso; Brazil